Vihanneslajikkeet Etelä-Savon tutkimusasemalla v. 1983-91 - Kivijärvi, Pirjo; Dalman, Pirjo; Valo, Ritva; Maatalouden tutkimuskeskus. Etelä-Savon tutkimusasema (Tiedote / Maatalouen tutkimuskeskus, ISSN 0359-7652, 1993)
Summary: Vegetable varieties tested at the South-Savo Research Station of the Agricultural Research Centre of Finland in 1983-1991.
Keywords: 1983-1991; vihannekset; lajikkeet; porkkana; kiinankaali; salaatti (salaattikasvit); lanttu; kukkakaali; punakaali; avomaaviljely; vihannesviljely; Etelä-Savo